A first course in the finite element method - Logan, Daryl L. (Cencage Learning, 2012)
Suitable for the undergraduate students in civil and mechanical engineering whose main interest is in stress analysis and heat transfer, this book provides a simple, basic approach to the course material that can be understood by both undergraduate and graduate students without the usual prerequisites (that is structural analysis)